2017
DOI: 10.1111/1742-6723.12885
|View full text |Cite
|
Sign up to set email alerts
|

Realism in paediatric emergency simulations: A prospective comparison of in situ, low fidelity and centre‐based, high fidelity scenarios

Abstract: Objective: To measure scenario participant and faculty self-reported realism, engagement and learning for the low fidelity, in situ simulations and compare this to high fidelity, centre-based simulations. Methods: A prospective survey of scenario participants and faculty completing in situ and centre-based paediatric simulations.Results: There were 382 responses, 276 from scenario participants and 106 from faculty with 241 responses from in situ and 141 from centre-based simulations. Scenario participant respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
13
1
1
Order By: Relevance
“…Another possible success factor might be that the crew, in order to minimize time-wasting, went straight from the HEMS base resting area to the brief for simulation and then straight into the simulation itself. We chose a basic manikin, which in a recent study was found to be as effective as a high fidelity manikin in inducing participant self-reported engagement and learning [18].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible success factor might be that the crew, in order to minimize time-wasting, went straight from the HEMS base resting area to the brief for simulation and then straight into the simulation itself. We chose a basic manikin, which in a recent study was found to be as effective as a high fidelity manikin in inducing participant self-reported engagement and learning [18].…”
Section: Discussionmentioning
confidence: 99%
“…Contar con un instrumento validado para medir los resultados de este programa podría ser parte de un proceso de posterior mejora. 25 Es posible que el entrenamiento de las habilidades técnicas y no técnicas en los escenarios de emergencia prehospitalaria se vea reflejada en una mejora global de los resultados clínicos y la calidad de atención de los pacientes y sus familias.…”
Section: Discussionunclassified
“…In addition, few studies exist on the importance of realism in simulation, but the importance of training in conditions close to real practice has already been shown. 32 For all these reasons, we are working in close partnership with important knowledge users from our institution towards a single, shared goal to improve patient safety. Publications in peer-reviewed journals and international conferences presentations are also planned.…”
Section: Dissemination Strategymentioning
confidence: 99%